2018
DOI: 10.1038/s41598-018-24294-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ultrasound bioimaging to predict worm burden and treatment efficacy in preclinical filariasis drug screening models

Abstract: Filariasis is a global health problem targeted for elimination. Curative drugs (macrofilaricides) are required to accelerate elimination. Candidate macrofilaricides require testing in preclinical models of filariasis. The incidence of infection failures and high intra-group variation means that large group sizes are required for drug testing. Further, a lack of accurate, quantitative adult biomarkers results in protracted timeframes or multiple groups for endpoint analyses. Here we evaluate intra-vital ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Through an extensive meta-analysis of 32 independent sub-periodic human strain B. malayi infection experiments undertaken in our laboratory between 2012-2018, including untreated or vehicle control data derived from published in vivo preclinical model development, drug screening or immunological investigations [6, 15, 18-20, 23, 25, 45-49], we determined that immunodeficient mouse strains serve as improved models for propagations of adults. Whilst we have previously described reduced variability of adult worm burden and less frequent occurrence of infection failures in CB.17 SCID mice compared with gerbils [18], we extend our conclusions here that CB.17 SCID mice afford a >3-fold more productive source of adult infections per unit inoculation. Improvements in yields become more pronounced with chronicity of infection with >10-fold increases in adult burdens in >25-week old infections.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Through an extensive meta-analysis of 32 independent sub-periodic human strain B. malayi infection experiments undertaken in our laboratory between 2012-2018, including untreated or vehicle control data derived from published in vivo preclinical model development, drug screening or immunological investigations [6, 15, 18-20, 23, 25, 45-49], we determined that immunodeficient mouse strains serve as improved models for propagations of adults. Whilst we have previously described reduced variability of adult worm burden and less frequent occurrence of infection failures in CB.17 SCID mice compared with gerbils [18], we extend our conclusions here that CB.17 SCID mice afford a >3-fold more productive source of adult infections per unit inoculation. Improvements in yields become more pronounced with chronicity of infection with >10-fold increases in adult burdens in >25-week old infections.…”
Section: Discussionsupporting
confidence: 87%
“…More recently, Severe-Combined ImmunoDeficient (SCID) mice, deficient in adaptive immunity, have been appraised as long-term fully susceptible hosts for B. malayi and the human filarial pathogen, Loa loa, and have been subsequently validated as drug screening models [15][16][17]. Brugia malayi infection success and variability in adult yields are more consistent in SCID mice compared with gerbils [18]. We have recently identified that adaptive immune control of B. malayi in mice is dependent on interleukin (IL)-4 receptor-alpha (Rα) macrophage activation mediating recruitment of a vigorous tissue eosinophilia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Infected animals were randomly assigned into dose groups with n = 3 to 7 for larval-stage testing and n = 4 to 9 for adult-stage testing. Randomization was done by stratification based on ID number (B. malayi larval and prefecund adult infections), baseline ultrasonography estimates of worm burden (B. malayi infection of SCID mice and gerbils) using a semi-quantifiable scoring system (26), baseline microfilariaemia (L. sigmodontis infection of gerbils), or order of implantation and source of male worms (O. ochengi implantation into SCID mice or gerbils).…”
Section: Treatment Of Infected Animals With Tylosin a Analogs And Ant...mentioning
confidence: 99%
“…After 6 days of drug exposure, mf were also tested for metabolic activity, a measure of parasite viability, using the MTT assay (Figure C). The MTT assay is part of the WHO-approved in vitro assay for antifilarial activity using O. gutturosa and has been previously used for assessment of B. malayi metabolic status. 1 and 14 in particular showed activity in this assay, significantly reducing B. malayi mf MTT reductase activity on average by 53 and 82%, respectively (one-way ANOVA with Holm–Sidak’s multiple comparison tests, P < 0.01 and P < 0.0001). The time course of the effect of 1 against mf motility at different concentrations is shown in Supplementary Figure 3.…”
Section: Resultsmentioning
confidence: 99%